Male breast cancer: clinical presentation, diagnosis, treatment - Hotko, Y.S. (Experimental Oncology, 2013)
Despite male breast cancer is rare in occurrence, it is a serious problem. In 2012, 130 men in Ukraine got breast cancer that constituted 0.74% from all patients with mentioned pathology detected in the course of year. Every year in Ukraine approximately 100 men die from breast cancer. Still many aspects of male breast cancer remain unstudied. It occurs since information about mentioned disease is mainly based on retrospective analysis of small groups. Treatment of men, who got breast cancer, is based on knowledge, which has been obtained in treatment of women with this pathology. This article is based on the results of analysis of 168 cases of breast cancer in men, who have been examined and treated in the period from 1956 to 2012. In paper the peculiarities of clinical manifestations of male breast cancer have been determined, the optimal volume of diagnostic procedures in men with suspicion of breast cancer has been established, the mammographic signs have been detected and the possible histological variants of disease have been determined, clinical course peculiarities of male breast cancer have been defined, the most essential factors of prognosis of the disease have been fixed. Furthermore, in article optimal volume of surgical treatment of male breast cancer has been substantiated, the role and place of radiotherapy in treatment of this pathology has been determined. It has been proved that adjuvant polychemotherapy should be applied to the patients with male breast cancer independently from stage of process. Also optimal schemes of this kind of treatment have been determined. The efficacy of hormonal therapy with antiestrogen in patients with positive receptors of steroid hormones and at presence of unfavorable prognostic factors of disease has been demonstrated. The inefficiency of orchiectomy as one of the widespread kinds of hormonal therapy of male breast cancer has been defined.